Numerical modelling of wave-induced vertical ship motions at the Port of Richards Bay : calibration and computation of extreme values - Sebopa, Mogau (Stellenbosch : Stellenbosch University, 2020)
Thesis (MEng)--Stellenbosch University, 2020.